Texture and mineralogical composition of Quaternary terrestrial and marine sediments from Macedonia and Thrace, Greece - Tsirambides, Ananias (Bulletin of the Geological Society of Greece, 2019)
Clastic sediments collected from land and gulfs of Macedonia and Thrace in Greece are examined on the basis of their texture and mineral composition. All terrestrial samples are coarse-grained and poorly sorted, with angular to sub-angular grains. These are mainly composed of quartz and feldspars, followed by micas, calcite and Fe-Mg minerals. Among the clay minerals illite predominates over smectite and smectite over vermiculite (+chlorite+kaolinite). In addition, the interstratified phases illite/smectite, chlorite/vermiculite, and smectite/vermiculite are present in significant amounts in the clay fraction (<2 μm), signifying the incomplete weathering of the primary minerals. Mixing during transportation, flocculation, differential settling processes and organic matter are the main mechanisms for the distribution of the discharged terrigenous load into the North Aegean Gulfs. All gulf bottom samples are coarse to fine grained and medium sorted, and their grains are angular to sub-angular. Quartz and feldspars predominate. In addition, biogenic calcite, micas and various Fe-Mg minerals exist as primary and/or accessory minerals. Among clay minerals, illite predominates over smectite and smectite over kaolinite (+chlorite+vermiculite). Almost in all gulf sediments the interstratified phase illite/smectite is apparent. The presence of feldspars and Fe-Mg minerals, as well as the high content of clay minerals and the polymodal grain-size distribution with angular to sub-angular grains, signify mineralogical and textural immaturity of all the examined sediments, as well as predominance of mild climatic conditions and thus mild weathering processes. The quartz content in these sediments is usually <70%. Therefore, a sedimentation cycle of these materials has not been completed.